2018
DOI: 10.5194/wes-2018-33
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online model calibration for a simplified LES model in pursuit of real-time closed-loop wind farm control

Abstract: Abstract. Wind farm control often relies on computationally inexpensive surrogate models to predict the dynamics inside a farm. However, the reliability of these models over the spectrum of wind farm operation remains questionable due to the many uncertainties in the atmospheric conditions and tough-to-model flow dynamics at a range of spatial and temporal scales relevant for control. A closed-loop control framework is proposed in which a simplified dynamical LES model is calibrated and used for optimization i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Here, we will employ the EnKF (Evensen, 2003) Doekemeijer et al, 2018;Mandel, 2009). The states and dimensions here represent the wake model instantiations and parameters, respectively.…”
Section: Ensemble Kalman Filter State Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will employ the EnKF (Evensen, 2003) Doekemeijer et al, 2018;Mandel, 2009). The states and dimensions here represent the wake model instantiations and parameters, respectively.…”
Section: Ensemble Kalman Filter State Estimationmentioning
confidence: 99%
“…The EnKF filter has been successfully used for low-order model state estimation for the purpose of receding horizon frequency regulation control (Shapiro et al, 2017) and reference power signal tracking applications (Shapiro et al, 2019). Doekemeijer et al (2018) found that the EnKF has comparable state estimation performance given either nacelle-mounted LiDAR data or Supervisory Control and Data Acquisition (SCADA) power production data alone. Since very few utility-scale wind turbines have nacelle-mounted LiDAR systems, the successful performance of the EnKF based on SCADA data alone highlights the potential for online model calibration without additional hardware installation.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, a simplified state estimation algorithm has been applied for dynamic surrogate models, such as a linear Kalman filter (e.g., [18], [27]). More recently, there have been positive developments in the field of real-time model adaptation, using more sophisticated estimation algorithms that attempt to balance accuracy with computational efficiency (e.g., [28], [29]). In terms of optimization, for steady-state surrogate models, a gradient-based or nonlinear optimization algorithm is typically employed to determine the optimal steady-state control settings for the wind farm (e.g., [8], [30], [31]).…”
Section: ) Online Estimation and Optimization Algorithm Designmentioning
confidence: 99%
“…Large-eddy simulation models such as SOWFA resolve larger scale flow dynamics directly, and employ a subgridscale model for smaller eddy dynamics. SOWFA has been used on multiple occasions for surrogate model calibration (e.g., [8], [20], [44]), model validation, and wind farm controller verification (e.g., [29], [34], [35], [44]).…”
Section: A Sowfamentioning
confidence: 99%
“…While such analytic models are lower in reliability than high fidelity simulations, they can accurately capture wind farm power production trends [4]. Low-order models are particularly relevant for the purpose of online control of wind farm power as a function of time for energy grid optimization (see, e.g., [42][43][44]) due to the computational expensive of online large-eddy simulations [45]. The physics-based, low-order model selected here is the Gaussian wake model [7] with the momentum theory prescribed by Prandtl's lifting line model [8].…”
Section: Physics-based Modelmentioning
confidence: 99%